Short-term outcomes of inborn vs out-born very low birth weight neonates (< 1500 g) in the Groote Schuur neonatal nursery - Gibbs, Lyndal (Division of Neonatology, 2018)
Background and aim: The Groote Schuur Hospital (GSH) Neonatal Nursery provides Level 3 care for the Metro West Health District in the Western Cape. Worldwide, VLBW neonates have improved outcomes when delivered in Level 3 neonatal units, compared with those who are transported from other facilities. This study aims to identify the characteristics and clinical outcomes of our VLBW patients, with emphasis on differences between inborns and outborns. Methodology: A retrospective cohort study. VLBW neonates admitted to the GSH Neonatal Nursery between 1 January 2012 and 31 December 2013 were enrolled on the Vermont Oxford Network database and reviewed. Maternal and infant characteristics, and outcomes at the time of discharge from hospital were analysed. Results: A total of 1032 VLBW neonates were enrolled. 906 (87.8%) were delivered at GSH, and 126 (12.2%) were outborn. Access to antenatal care, antenatal steroids and inborn status were statistically significant predictors for mortality and survival without morbidity. The mothers of inborn patients were more likely to have received antenatal care (89.1% vs 57.9%, p <0.0001) and antenatal steroids (64.2% vs 15.2%, p <0.0001). Inborns required less ventilatory support (16.2% vs 57.9%, p <0.0001) and surfactant administration (25.3% vs 65.1%, p <0.0001). Inborns had a lower incidence of late infection (8.8% vs 23.4%, p <0.0001), severe intraventricular haemorrhage (3.7% vs 13.9%, p <0.0001) and chronic lung disease (5.3% vs 13.4%, p =0.003). The incidence of necrotising enterocolitis was similar between the two groups (5.9% vs 8.7%, p =0.227). 18.4% of inborns and 33.3% of outborns demised (p <0.0001), mostly on the first 2 days of admission. Mortality declined as birth weight increased. Of the survivors, 83.5% of inborns and 70.2% of outborns did not develop serious morbidity (p =0.003). Significant morbidity and mortality was noted in the outborn group weighing 800g and less, with only one outborn patient in the cohort surviving to discharge without major morbidity. Conclusion: VLBW neonates delivered at Groote Schuur Hospital had better outcomes than their outborn counterparts. Perinatal regionalisation is beneficial to our patients, with antenatal care, timeous in-utero transfer and antenatal steroids contributing to excellent outcomes.